Experimental study on ash content & calorific value of coal used in thermal power station. (2021) - Balachandar, V.; Ramkumar, T.; Kalidasan, B.; Subramaniyan, C.
Abstract: Electricity has become a most important parameter for developing countries to improve their growth rate. On an average in India power generation is contributed using coal as fuel up to 75.9%. Higher the calorific value, higher would be the heat liberated from the coal, thus resulting in higher steam generation, which would contribute to increase in power generation. In this article experimental attempt has been made to study the performance of coal used in Indian thermal power plant in terms of calorific value and ash content. Coal used in Chandrapur super thermal power station was blended with charcoal of Prosopis Juliflora in proportion of 100, 80, 60, 40 and 20 percentage. Preparation of coal was also differentiate by crushing the coal manually and using ball miller. Result shows that blending coal with charcoal of Prosopis Juliflora showed increase in calorific value and decrease in ash content.